2000
DOI: 10.1038/sj.cdd.4400588
|View full text |Cite
|
Sign up to set email alerts
|

Cripto-1 induces apoptosis in HC-11 mouse mammary epithelial cells

Abstract: Cripto-1 (CR-1) is an epidermal growth factor (EGF)-related protein. CR-1 can inhibit b-casein and whey acidic protein expression in mouse mammary epithelial cells. The present study demonstrates that CR-1 can induce apoptosis in HC-11 mouse mammary epithelial cells, as measured by bisbenzimide stained nuclei, TUNEL assay and cell death ELISA. Apoptosis could be observed after 2 days of exposure of confluent HC-11 cells to CR-1 in the absence of the survival factors EGF and insulin, with maximum apoptosis occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Similar to our results with EGF, heregulin also enhanced the degradation of PARP but unlike EGF, heregulin activated caspase 9 without any significant activation of caspase 3 (51). Cripto-1 mediates the induction of caspase 3-like protease and downregulates the expression of Bcl-XL (15). UCVA-1 cells, derived from human pancreas adenocarcinoma, have a high number of EGFRs but their growth is not inhibited by EGF, highlighting the complexity of the mechanisms involved in EGF-induced apoptosis (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results with EGF, heregulin also enhanced the degradation of PARP but unlike EGF, heregulin activated caspase 9 without any significant activation of caspase 3 (51). Cripto-1 mediates the induction of caspase 3-like protease and downregulates the expression of Bcl-XL (15). UCVA-1 cells, derived from human pancreas adenocarcinoma, have a high number of EGFRs but their growth is not inhibited by EGF, highlighting the complexity of the mechanisms involved in EGF-induced apoptosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors other than EGF such as platelet-derived growth factor and hepatocyte growth factor can also trigger cell cycle arrest and death in a variety of cells (13,14) and in addition, EGF enhanced the apoptotic effect of platelet-derived growth factor (14). An EGF-related protein, Cripto-1, promotes apoptosis in HC-11 mouse mammary epithelial cells (15). Anoikis, activation of EGFR tyrosine kinase, Ras-MAP kinase signaling, and the elevation of Stat1 and p21 levels have been advocated as mechanisms driving EGF-induced apoptosis (11, 16 -18) but, the actual mechanism appears to be more elusive and complicated.…”
mentioning
confidence: 99%
“…The elucidation of the signals and transcriptional events underlying the up-regulation of Cripto expression in these tumors remains an important area of future research. With regard to Cripto's mechanism(s) of action, it has been shown that recombinant, soluble Cripto can activate both the p42 mitogen-activated protein kinase pathway (40) and the phosphatidylinositol 3-kinase pathway (41) in mammary epithelial cells through an unidentified receptor. The ability of Cripto to activate these pathways, which are frequently growth-stimulatory in nature, may at least partially explain its effects on cell growth, differentiation, and oncogenesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the case since we have found recently that CR-1 can induce apoptosis in several nontransformed mouse mammary epithelial cell lines. Apoptosis could be observed after 2 days exposure of confluent HC-11 cells to CR-1 when cells were deprived of the survival factors, EGF and insulin (De Santis et al 2000). Apoptosis was mediated through the induction of a caspase-3-like protease and down-regulation in the expression of the anti-apoptotic protein Bcl-x L .The induction of apoptosis under reduced serum by CR-1 was preceded by an inhibition in cell growth and a reduction in poly(ADP-ribose) polymerase (PARP) protein and an increase in β-catenin cleavage.…”
Section: In Vitro Effects Of Transduced Cr-1 or Recombinant Cr-1 In Mmentioning
confidence: 99%
“…Apoptosis was mediated through the induction of a caspase-3-like protease and down-regulation in the expression of the anti-apoptotic protein Bcl-x L .The induction of apoptosis under reduced serum by CR-1 was preceded by an inhibition in cell growth and a reduction in poly(ADP-ribose) polymerase (PARP) protein and an increase in β-catenin cleavage. A reduction in β-catenin levels due to caspase-3-mediated degradation may result in a loss of cell-cell and cell-matrix interactions with an increase in anoikis (De Santis et al 2000). Cr-1 has also been demonstrated to act as a survival factor in CID-9 cells transfected with a Cr-1 expression vector when cells were propagated under sparse, subconfluent conditions in medium containing low serum and insulin (Niemeyer et al 1998).…”
Section: In Vitro Effects Of Transduced Cr-1 or Recombinant Cr-1 In Mmentioning
confidence: 99%